2019
DOI: 10.1016/j.seizure.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Valproate utilisation trends among girls and women from 2013 to 2018

Abstract: To evaluate the change in the number of female valproate users in Lithuania from 2013 to 2018 and determine the presumed impact of two distinct European Medicines Agency (EMA) regulatory interventions on the observed trend. Method: An interrupted time series analysis was performed using reimbursement data from the National Health Register Fund to detect changes in user trends after a selected regulatory event in time. Results: The absolute number of female patients under 50 using valproate is seen decreasing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…Most reports on population-based temporal trends in VPA use by young females in the period after the EMA restrictions originate from Nordic countries [4][5][6][7]. One report originate from Lithuania, where a general decrease in VPA use was found for females aged < 50 years from 2013 to 2018; however, no significant impact of the 2014 EMA restriction on the number of patients using the drug was found [8]. No report describes trends in southern Europe, where the medical community's awareness of VPA's harmful effects could differ significantly from that in other European regions due to differences in the historical development of health care systems.…”
Section: Effects Of the 2014 Ema Restrictionsmentioning
confidence: 99%
“…Most reports on population-based temporal trends in VPA use by young females in the period after the EMA restrictions originate from Nordic countries [4][5][6][7]. One report originate from Lithuania, where a general decrease in VPA use was found for females aged < 50 years from 2013 to 2018; however, no significant impact of the 2014 EMA restriction on the number of patients using the drug was found [8]. No report describes trends in southern Europe, where the medical community's awareness of VPA's harmful effects could differ significantly from that in other European regions due to differences in the historical development of health care systems.…”
Section: Effects Of the 2014 Ema Restrictionsmentioning
confidence: 99%
“…To date, the findings from valproate utilisation studies from other European countries have revealed differences in the impact of the 2014 intervention at the individual‐country level. In Lithuania, a valproate utilisation study reported a general decrease in valproate for females under 50 years, but failed to report any significant impact of the 2014 EMA restrictions other than a delayed decrease in use among girls under 15 years 31 . A drug utilisation study conducted in Stockholm examined the impact of the 2014 EMA regulatory intervention on initiations of valproate, and reported a significant decline among women aged ≤45 years with a psychiatric disorder, but not epilepsy 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In Lithuania, a valproate utilisation study reported a general decrease in valproate for females under 50 years, but failed to report any significant impact of the 2014 EMA restrictions other than a delayed decrease in use among girls under 15 years. 31 A drug utilisation study conducted in Stockholm examined the impact of the 2014 EMA regulatory intervention on initiations of valproate, and reported a significant decline among women aged ≤45 years with a psychiatric disorder, but not epilepsy. 21 In contrast, the recent Estonian utilisation study reported the decline in prescribing following the 2014 intervention to be among neurologists, and not psychiatrists.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The study design was similar to that used by Puteikis et al to assess the impact of the EMA regulation on VPA use (Puteikis et al, 2019). To evaluate changes in the numbers of PD patients treated with TMZ, new prescriptions on TMZ and withdrawal of the drug in PD over time, the analysis of an interrupted time series model was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to TMZ in PD, the EMA took regulatory actions for valproic acid (VPA) use in girls, women of childbearing age, and pregnant females based on postmarketing data. Although the efficacy of the restrictions on VPA use by the EMA has been thoroughly evaluated ( European Medicines Agency, 2014 ; Vajda et al, 2014 ; Wen et al, 2015 ; Liu et al, 2017 ; Karlsson Lind et al, 2018 ; Kinney et al, 2018 ; Virta et al, 2018 ; Jacob et al, 2019 ; Puteikis et al, 2019 ), only little efforts have been made to generate such information concerning the impact of the EMA warning on the clinical practice with TMZ thus far ( von Bredow et al, 2018 ). Therefore, we conducted a study in Hungary, a country in the European Union with a population of ∼10 million of which ∼400,000 inhabitants suffered from stable coronary heart disease in 2018 ( Pintér et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%